Analysis of the Influence of Training, Discipline and Safety on the Performance of Medan City Fire Department Officers - Theo Filus Ndruru; Melinda Siregar; Mei Lina Panjaitan; Ratna Rovita Sari Purba; Hasrita Lubis (PT FORMOSA CENDEKIA GLOBAL, 2023)
Firefighters, abbreviated as DAMKAR, are implementing elements of the government that have the responsibility to assist the community in handling fires. In the city of Medan, especially this fire fighting unit is in the Public Works Department of the Municipality of Medan, which is in one of the sections and is called the Municipal Fire Prevention Unit. The research approach is quantitative. Based on the results of the analysis and interpretation, the researchers concluded that the effect of training and safety on performance has a positive and significant influence. In contrast to discipline, which does not have a positive influence on employee performance because discipline affects obedience to rules and norms in order to increase employee morale. In this case, we can understand that if training and safety are further improved, the performance of the Medan city fire service officers will be more efficient, and by providing awareness of good discipline, they will also be able to provide a good view of the surrounding community towards Medan city fire service officers.